A pH-responsive liposomal nanoplatform for co-delivery of a Pt(IV) prodrug and cinnamaldehyde for effective tumor therapy - Tang, Ting; Gong, Yufang; Gao, Yuan; Pang, Xinlong; Liu, Shuangqing; Xia, Yulan; Liu, Dongsheng; Zhu, Lin; Fan, Qing; Sun, Xiao (Frontiers in Bioengineering and Biotechnology, 2023)
The tumor microenvironment (TME) is mainly characterized by abnormally elevated intracellular redox levels and excessive oxidative stress. However, the equilibrium of TME is also very fragile and susceptible to be broken by external factors. Therefore, several researchers are now focusing on intervention in redox processes as a therapeutic strategy to treat tumors. Here, we developed a liposomal drug delivery platform that can load a Pt(IV) prodrug (DSCP) and cinnamic aldehyde (CA) in a pH-responsive liposome to enrich more drugs in the tumor region for better therapeutic efficacy through enhanced permeability and retention effect, causing less damage to the surrounding normal tissues compared to that achieved with conventional drugs. DSCP delivered to the tumor region can deplete glutathione in the TME to generate highly toxic cisplatin. While CA, a common antitumor drug, can promote the production of reactive oxygen species, further causing a redox imbalance in the TME. Thus, in this study, the novel liposome nanomedicine loaded with DSCP and CA offers a synergistic strategy of conventional chemotherapy and the disturbance of TME’s redox homeostasis, leading to a significant increase in antitumor effects.